Identification and Evaluation of Antigens for Sarcoma Immunotherapy - Birdi, Harsimrat Kaur (Université d'Ottawa / University of Ottawa, 2022)
Cancer immunotherapies focused on tumor-specific T cell responses are promising alternatives to chemotherapy/radiotherapy for various cancers as they can be engineered to specifically target tumours and establish long-term surveillance against relapsing tumours. The premise for the application of active immunotherapies is the recognition of tumor-specific and/or tumor-associated antigens by the immune system. Approaches that have been explored to this end include cancer vaccines and gene therapy/autologous cell transfer (T-cell receptor (TCR) or chimeric antigen receptor (CAR)-based). This study evaluated the use of oncolytic rhabdovirus-based vaccines (ORV) for the treatment of sarcoma with a focus on rhabdomyosarcoma (RMS). Sarcomas are amenable to to oncolytic virus (OV) infection and generate robust T-cell responses against tumour antigens. The ORV strategy undergoing clinical evaluation uses a prime-boost vaccine whereby a non-replicating adenovirus serotype 5 vector (Ad5) encoding an antigen is administered as a priming agent and boosted with a rhabdovirus encoding the same antigen (NCT02285816). However, the prevalence of pre-existing immunity to Ad5 in patients serves as an exclusion criterion and limits its effectiveness as a priming agent. To this end, we have shown that an alternative priming agent and antigen delivery vehicle, anti-DEC205 (aDEC205), targets antigens directly to dendritic cells (DCs), inducing robust immune responses. However, a lack of targetable antigens and methods to identify antigens is a limiting step for the application of ORVs for sarcoma. Thus, the identification of immunogenic sarcoma antigens is a critical step for the study ORVs. Current methodologies have important drawbacks in that they can be prohibitively time-consuming, complex or are ineffective in coupling antigen discovery and immunogenicity. Presented herein is the study of a novel methodology for the discovery of immunogenic antigens by probing for T cell activation marker CD107a and isolation by flow cytometry. In parallel, RMS antigen discovery was also performed via peptide elution and mass spectrometry resulting in the identification of 24 novel murine RMS antigens. Ultimately, therapeutic vaccination with a subset of these antigens encoded into DEC205 and ORV did not yield immune responses in a pre-clinical model; however, this research established immunization tools for further study of immunotherapy in RMS.
Keywords: Immunotherapy; Cancer; Vaccines; Rhabdomyosarcoma; Cancer Antigens